Air-conditioner Power Supply for CRH380A EMUs - LIU Fanghua; TANG Juan; LIN Chaoyong; WEI Wenhai (机车电传动)
Technical parameters, main circuit, control method, overall structure and characteristics of air-conditioner power supply for CRH380A EMUs was introduced. At the same time, combined with its particular use environment, some methods of reliability design were elaborated. At last, a series of reliability test was carried out to validate the effectiveness of the design method.